Exploring the link between Paradoxical leadership and nurses’ career maturity: the mediating role of organizational learning - Amal Diab Ghanem Atalla; Wafaa Hassan Mostafa; Mohamed Saad Saleh Ali (BMC Nursing)
Abstract Background Paradoxical leadership, which strikes a balance between control and flexibility, is becoming more and more acknowledged as being essential for promoting nurses’ career maturity, adaptation, and continuous development in today’s complicated healthcare environments. Nevertheless, little is known about the processes that connect leadership traits to professional development, especially the part played by organizational learning. Aim This study aimed to evaluate nurses’ professional maturity and perceived paradoxical leadership, to investigate their relationship, and to determine the mediating role of organizational learning in this relationship. Design Following STROBE criteria, a descriptive cross-sectional design was employed. Methods and tools A descriptive cross-sectional study was carried out at a general hospital in Egypt with 380 nurses. Participants filled out the Organizational Learning Scale, the Career Maturity Questionnaire, and the Paradoxical Leadership Scale (PLS). Following STROBE principles, data were analyzed using ANOVA, Pearson correlation, and structural equation modeling (SEM). Results High degrees of organizational learning, professional maturity, and paradoxical leadership were noted by nurses. All of the factors showed significant positive relationships with one another. Both career maturity (β = 0.144, p = 0.004) and organizational learning (β = 0.136, p = 0.007) were directly impacted by paradoxical leadership. Additionally, organizational learning moderated the association between leadership and career maturity (indirect effect = 0.0245; total effect = 0.756) and had a direct influence on career maturity (β = 0.180, p < 0.001). An excellent fit was shown by the model fit indices (CFI = 1.000, IFI = 1.000, RMSEA = 0.073). Conclusion Nurses’ career maturity is greatly increased by paradoxical leadership, with organizational learning serving as a crucial mediating factor. Enhancing these elements through learning programs and leadership development can benefit nurses’ career development and patient outcomes. Clinical trial number Not relevant.